Long term (3 years) weight loss after low intensity endurance training targeted at the level of maximal muscular lipid oxidation. (26th March 2018) - Drapier, Edelweiss; Chérif, Amira; Richou, Marlène; Bughin, François; Fédou, Christine; Mercier, Jacques; Avignon, Antoine; Brun, Jean-Frédéric
No abstract available